Preparation and properties of epoxy/BN highly thermal conductive composites reinforced with SiC whisker. Issue 9 (5th April 2015) - Tang, Dahang; Su, Juqiao; Kong, Miqiu; Zhao, Zhongguo; Yang, Qi; Huang, Yajiang; Liao, Xia; Niu, Yanhua
Abstract : A simple method is reported to increase the thermal conductivity and improve the poor mechanical properties caused by high filler loadings of epoxy composites, simultaneously. Epoxy composites were prepared with micro‐boron nitride (BN) and silicon carbon whisker (SiCw) chemically treated by 3‐aminopropyltriethoxysilane (KH550) and 3‐glycidyloxypropyltrimethoxysilane (KH560), respectively. Effects of surface modification of BN particles on the thermal conductivity and flexural strength of epoxy/BN composites were investigated. About 3% SiCw particles grafted with KH560 were incorporated into composites with BN grafted with KH550, which led to about 13.8–17.8% increase of the flexural strength as well as a marginal improvement of the thermal conductivity of composites, and they possessed good dielectric properties. In addition, dynamic mechanical analysis results showed that the storage modulus of composites increased significantly with the addition of fillers, while the glass transition temperature exhibited a slight decrease. POLYM. COMPOS., 37:2611–2621, 2016. © 2015 Society of Plastics Engineers